Seed transmission rates of Pea seed-borne mosaic virus among lentil genotypes in Ethiopia - Ademe, Anteneh; Kumari, Safaa; Moukahel, Abdulrahman; Kemal, Seid Ahmed; Aynewa, Yetsedaw (International Center for Agricultural Research in the Dry Areas, 2023)
Evaluation of Pea seed-borne mosaic virus (PSbMV, genus Potyvirus, family Potyviridae) seed transmission rate among 62 different lentil genotypes was carried out during 2021-2023 at Amhara Regional Agricultural Research Institute, Bahir Dar, Ethiopia. Seed transmission rates among lentil genotypes ranged from 0.0 to 36.4%. Released lentil varieties (Alemaya and Derso) showed high levels of seed transmission rates (13.5% and 7.1%, respectively). The finding can help lentil breeders to develop PSbMV resistant varieties with low seed transmission rates to combat the disease and expand lentil production in the highlands of Ethiopia.